RETINOPATHY OF PREMATURITY (ROP) - Qadir, Afzal (Khyber Journal of Medical Sciences, 2025)
Introduction Retinopathy of Prematurity (ROP) is a potentially blinding eye disorder that primarily affects premature infants. This condition is significant not only because of its impact on the individual lives of these infants and their families but also due to the broader implications for our healthcare system and society. Raising awareness and understanding the importance of early detection and intervention can significantly alter the course of ROP, offering a brighter future for those affected [1]